Platoon-based cyclists cooperative system (2015)
Bicycle use has steadily risen its share of total urban traffic over the last decade. This has been the result of city governments promotion of alternative forms of transportation, in the search for finding strategies that help reduce traffic congestion. Although benefits of cycling in congestion and pollution are concrete, in several cities the increment of cyclists has gotten to the point to overflow the infrastructure, deriving in safety risks and gridlocks due to the lack of explicit coordination among cyclists. This paper presents the integration of two strategies that so far have been considered completely independent: cooperative driving and cycling. Our project addresses the coordination of collective behavior of platoons of cyclists that could pervade dedicated express roads such as the London's 18 mile East-West Cycle Superhighway. The proposed platoon-based cyclists cooperative system can be defined as a networked cyber-physical system with an additional challenge related to the human factor.